Preoperative evaluation of endoscopic thyroidectomy via the total areola approach (ETA): a fluid-structure interaction model for predicting lymph node clearance and surgical suitability - Li, Ping; Du, Yuheng; Wang, Xudong; Shi, Yu; Ye, Chongyang; Jin, Rui (Frontiers in Bioengineering and Biotechnology, 2025)
The global increase in thyroid cancer incidence has driven the adoption of minimally invasive techniques, such as endoscopic thyroidectomy via the total areola approach (ETA), which is widely used in China. However, concerns persist regarding the completeness of central lymph node dissection (CLND) in ETA due to anatomical constraints (e.g., clavicle and sternum), which may obscure the surgical view of the upper diaphragm (level VII, defined as the region between the clavicular surface and innominate artery). Clinical reports of residual/recurrent lymph nodes in ETA patients underscore the need for precise preoperative evaluation. We retrospectively analyzed 513 patients with T1–T2 thyroid cancer (178 ETA, 335 open surgery) who underwent CLND. Preoperative CT imaging was used to construct a fluid-solid interaction model simulating tissue deformation and stress under 0.5–2 N traction forces, with innominate artery flow velocities predicted computationally. Patients were stratified by clavicle-to-innominate artery distance: <5 mm, 5–13 mm, and >13 mm. No significant difference in lymph node yield was observed between the <5 mm and 5–13 mm groups compared to open surgery. However, the >13 mm group had significantly fewer dissected nodes (p < 0.05), with three recurrence cases during follow-up. ETA achieves oncologic outcomes comparable to open surgery for patients with clavicle-to-innominate artery distances <13 mm. Beyond this threshold, incomplete dissection may occur, suggesting preoperative CT assessment of this anatomical parameter could guide surgical approach selection.